Innovative approaches to the treatment of local recurrent vulvar cancer in patients with lichen sclerosus - A. V. Zharov; E. G. Novikova; A. G. Rerberg; E. V. Kolesnikova (ABV-press, 2023)
Background. In recent years, there has been an increase in the incidence of vulvar precancer (lichen sclerosus), as well as vulvar cancer. Since this disorder is rare, treatment planning and therapy itself are often suboptimal, which results in a high recurrence rate. Treatment of patients with local recurrence is even more difficult. Improper therapy often leads to fatal outcomes.Aim. To develop an innovative therapeutic approach to local recurrent vulvar cancer that includes combination (intraarterial and systemic) chemotherapy and surgery.Materials and methods. This pilot study included two patients with a second episode of local recurrent vulvar cancer. The first patient was denied special treatment, whereas the second one was offered abdominoperineal resection of the rectum. At the first stage, the patients received combination chemotherapy; at the second stage, they had combination reconstructive surgeries.Results. Combination chemotherapy was highly effective as demonstrated by the reduction of the recurrent tumor to a resectable size. Combination and reconstructive surgeries allowed us to preform radical treatment and preserve functions of the adjacent organs.Conclusion. Combination treatment was highly effective in patients with local recurrent vulvar cancer, when the tumor was located near the urethra, vagina, and anus or invaded them. Combination chemotherapy ensured good tumor regression, while surgery gave hopes for a favorable outcome.